2022
DOI: 10.1038/s44161-022-00140-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal transcriptome analysis reveals critical roles for mechano-sensing genes at the border zone in remodeling after myocardial infarction

Abstract: The underlying mechanisms of ventricular remodeling after myocardial infarction (MI) remain largely unknown. In this study, we performed an integrative analysis of spatial transcriptomics and single-nucleus RNA sequencing (snRNA-seq) in a murine MI model and found that mechanical stress-response genes are expressed at the border zone and play a critical role in left ventricular remodeling after MI. An integrative analysis of snRNA-seq and spatial transcriptome of the heart tissue after MI identified the unique… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Interestingly, the loss of neighboring cardiomyocytes in vitro (scratch assay) increased the expression of the same mechano-sensing genes in cardiomyocytes, supporting the loss of neighbor hypothesis. 52 In accordance with these findings, Yamada et al 51 observed increased gene expression of mechano-sensing genes in the border zone. They identified the mechano-sensing gene cysteine and glycine-rich protein 3 ( Csrp3 ) as a regulator of post-MI remodeling in the border zone after MI.…”
Section: Recent Findings Using Spatial Multiomics Approachesmentioning
confidence: 55%
See 2 more Smart Citations
“…Interestingly, the loss of neighboring cardiomyocytes in vitro (scratch assay) increased the expression of the same mechano-sensing genes in cardiomyocytes, supporting the loss of neighbor hypothesis. 52 In accordance with these findings, Yamada et al 51 observed increased gene expression of mechano-sensing genes in the border zone. They identified the mechano-sensing gene cysteine and glycine-rich protein 3 ( Csrp3 ) as a regulator of post-MI remodeling in the border zone after MI.…”
Section: Recent Findings Using Spatial Multiomics Approachesmentioning
confidence: 55%
“…Concerning cardiovascular research, only studies using sequencing-based spatial transcriptomics investigating MI have been published yet. [46][47][48][49][50][51][52]…”
Section: Atvb In Focus -Vbmentioning
confidence: 99%
See 1 more Smart Citation
“…1I, methods ). The spatial position of these clusters indicates that they correspond to the infarct zone (with scar components such as: Col1a1 , Col3a1, Fn1 ), remote zone (with functional cardiomyocyte marker genes such as: Myh6, Myl2 ) and a defined border zone population between them (with marker genes such as Nppa , Ankrd1 and Clu) (Calcagno et al, 2022; Duijvenboden et al, 2019; Yamada et al, 2022) ( fig. S1D-E, Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…These techniques are on the rise due to the large amount of information provided. Recently, two studies have been published where spatial multiomics data reveal the molecular differences in myocardium after MI in human and mouse [ 7 , 8 ]. However, in the field of cardiology, although the porcine model is an excellent tool to evaluate the efficacy of different therapies, its use in “omics” studies has been limited by an incomplete annotation of the pig genome.…”
Section: Introductionmentioning
confidence: 99%